2018
DOI: 10.1002/ana.25302
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Intrathecal Mesenchymal Stem Cells for Amyotrophic Lateral Sclerosis

Abstract: ObjectiveTo assess the safety and efficacy of 2 repeated intrathecal injections of autologous bone marrow–derived mesenchymal stem cells (BM‐MSCs) in amyotrophic lateral sclerosis (ALS).MethodsIn a phase 2 randomized controlled trial (NCT01363401), 64 participants with ALS were randomly assigned treatments (1:1) of riluzole alone (control group, n = 31) or combined with 2 BM‐MSC injections (MSC group, n = 33). Safety was assessed based on the occurrence of adverse events. The primary efficacy outcome was chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 36 publications
5
107
0
4
Order By: Relevance
“…In particular, in ALS, mesenchymal stem cells have also been used as therapeutic agents to ameliorate disease progression 20 . To date, many studies have shown that mesenchymal stem cells administered into the central nervous system, skeletal muscles or both exert positive effects on lifespan and motor function in disease models 5,7,21 . Although Intramuscular injections of hUCB-MSCs have no effect on survival of motor neurons in the spinal cord of SOD1 transgenic mice (Supplement Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, in ALS, mesenchymal stem cells have also been used as therapeutic agents to ameliorate disease progression 20 . To date, many studies have shown that mesenchymal stem cells administered into the central nervous system, skeletal muscles or both exert positive effects on lifespan and motor function in disease models 5,7,21 . Although Intramuscular injections of hUCB-MSCs have no effect on survival of motor neurons in the spinal cord of SOD1 transgenic mice (Supplement Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During ALS disease progression, the loss of neuromuscular junction and muscle atrophy are critically related to disease progression 4 . However, most studies have focused on the central nervous system, especially on the motor neurons, as the main targets to improve disease progression and survival [5][6][7] . As mentioned above, due to the dynamic communication of various cells involved in disease progression, such approaches that only focus on motor neuron death are not effective for developing therapeutic agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although interventions with anti-inflammatory drugs in experimental neurodegenerative animal studies have not resulted in successful clinical trials, a more recent approach to treat such disorders, in both experimental animals and humans, with implanting bone marrowderived stromal cells (bm-SCs), seems very promising. Such transplants supposedly modulate the immune system in both acute (Deda et al 2008;Martinez et al 2017;Tsai et al 2018;Cofano et al 2019;Jin et al 2019) and chronic (Mazzini et al 2016;Ciervo et al 2017;Gashmardi et al 2017;Sykova et al 2017;Cizkova et al 2018;Garbuzova-Davis et al 2018;Oh et al 2018;Gugliandolo et al 2019) neurodegenerative disorders in experimental animals as well as in patients. Our own experiments with human bm-SC in experimental animal models of both an acute (traumatic spinal cord injury; tSCI) (de Munter et al 2019a;Romero-Ramirez et al 2020) and a chronic neurodegenerative disorder (amyotrophic lateral sclerosis; ALS) (de Munter et al 2019b) were fully in line with these findings.…”
Section: Interventions With Bm-derived Stromal Cells In Neurodegeneramentioning
confidence: 99%
“…Ho et al reported on 33 patients who received two doses (1 × 10 6 cells/kg) of IT MSCs 1 month apart. Changes in the Amyotrophic Lateral Sclerosis Functional Rating Scale‐Revised score from baseline to 4 and 6 months after injection were significantly different from the non‐MSC‐treated group . There were also significant changes in CSF cytokines with increases in levels of transforming growth factor‐ beta 1 and decreases in monocyte chemoattractant protein‐1 in the treated individuals possibly indicating an anti‐inflammatory effect …”
Section: Discussionmentioning
confidence: 99%